Endoplasmic Reticulum Stress of Oral Squamous Cell Carcinoma Induces Immunosuppression of Neutrophils - Wu, Ching-Fang; Hung, Tzu-Ting; Su, Yu-Chieh; Chen, Po-Jen; Lai, Kuei-Hung; Wang, Chih-Chun (Frontiers in Oncology, 2022)
The endoplasmic reticulum (ER) stress of cancer cells not only determined cancer cell fate but also indirectly triggered proinflammatory or immunosuppressive responses of macrophages. In addition, ER stressed neutrophils were known to acquire immunosuppressive activity with surface expression of lectin-like oxidized low-density lipoprotein receptor-1 (LOX-1). Since the importance of tumor ER stress and immunosuppressive neutrophils has been emphasized in head and neck cancers, we hypothesized that the ER stress of oral squamous cell carcinoma (OSCC) could transform neutrophils into LOX-1 expressing immunosuppressive phenotype. Two human OSCC cell lines, SCC25 and OML1, were treated with either vehicle or thapsigargin (THG), an ER stress inducer. These tumor conditioned media (TCM) were collected accordingly. Then human peripheral blood neutrophils from healthy donors were cultured in these TCM. The results showed that neutrophils cultured in THG-treated TCM had higher expression of LOX-1 compared with those cultured in vehicle-treated TCM. Moreover, by interleukin-2/anti-CD3/anti-CD28 activated autologous T cell proliferation assay, neutrophils conditioned by THG-treated TCM were shown to inhibit T cell proliferation more significantly than those conditioned by vehicle-treated TCM. These novel findings indicated that the ER stress of OSCC could be transmitted to neutrophils which in turn expressed LOX-1 and obtained immunosuppressive ability. Our findings further supported the existence of “transmissible” ER stress between tumor cells and neutrophils.